Dolls of Canada : a reference guide - Strahlendorf, Evelyn Robson (University of Toronto Press, 1990)
For the ardent collector and (or anyone who once owned a doll, here is a history of the dolls that have been made and loved in Canada. Doll collecting, a popular pursuit in Europe and the United States, has been growing rapidly in Canada. Evelyn Strahlendorf has compiled a reference work that traces the development of dolls in Canada and of the industry that produces them. It contains the dates, names, and characteristics of about 1000 Canadian dolls from prehistoric times to the present. Coverage begins with Inuit and other native dolls, then turns to the dolls that have survived from the days of early European settlement and the dolls of several of the ethnic cultures which make the Canadian mosaic. Much of the book is devoted to the work of commercial dollmakers and the evolution of their dolls, including the history of each company with information about their products, progress, and achievements. The manufacturing process is examined as it developed from bisque and composition through various plastics to the dolls of today. Separate chapters deal with dolls that portray celebrities (including Barbara Ann Scott, the Dionne quintuplets, and Wayne Gretsky), dolls that are more than playthings (used in displays or advertising), the Eaton's Beauty dolls that were the most popular dolls in Canada for many years, and dolls created by artists. The dolls reflect the changing fashions and culture of Canada. Their clothing is often the latest in style and materials; their abilities not only include talking, wiggling, and drinking but in recent years extend to bilingualism. With few exceptions, every doll described has been personally examined by the author. This book is a valuable reference tool for doll collectors, museums, libraries, antique dealers, doll stores, and flea market operators. Because Canada has been exporting dolls for half a century, it will benefit collectors internationally as well. It is also intended for a special class of enthusiast Mrs. Strahlendorf calls the closet collector. There are tens of thousands of such people in North America who have dolls and may collect dolls but do not admit their pleasure to others.